Antenna for MIMO systems - Tuan, Tran Minh; Linh, Bui Le Phuong (VNU Journal of Science: Natural Sciences and Technology, 2011)
Abstract . This paper concentrates on studying, designing and manufacturing a three port antenna applied for MIMO systems. This antenna can work in 2.4 GHz and 5.2 GHz frequencies, which are used for WLAN. Antenna is printed on FR4 substrate with size of 50 mm x 50 mm, thickness of 1.2 mm and relative permittivity of 4.4. The propose antenna is experimentally studied. Keywords: MIMO  antennas, Three ports antenna, antennas for WLAN.